Optimization of chlorophyll extraction from pineapple plantation waste - Siti Hajar, Abd Rahim; Norazwina, Zainol; Kamaliah, Abdul Samad (Elsevier Ltd, 2022)
The abundance of pineapple waste generated in Malaysia has becomes a serious issue as it puts our environment in grave danger. The presence of chlorophyll in pineapple waste has attracted many researchers to produce a natural dye from chlorophyll as a sensitizer for solar cells. Natural dyes can be considered a promising substitute for synthetic dyes as they are more environmentally friendly and cost less when compared to the synthetic dyes that are currently available on the market. This research aims to optimize the conditions of chlorophyll extraction from pineapple leaves using a mechanical extraction method. A response surface methodology was used to design an experimental design table using a central composite design based on two significant factors. The extraction cycle and the storage time varied between 1 and 5 cycles and 7 and 9 h, respectively, were studied. From the study, the maximum concentration of total chlorophyll (TC) was 693.292 mg/L. The optimum conditions for extraction cycle and storage time were at 3 cycles and 8 h, respectively. Among those two factors, it has been discovered that the storage time has a smaller p-value (p = 0.1106) than the extraction cycle, indicating that this factor was the critical factor affecting the TC concentration. The value of R2 for the analysis was 0.8673, making the analysis a well-fitted model. Thus, it has been established that the models are suitable for optimizing the extraction conditions in order to maximize the concentration of TC using the mechanical method.